German vocabulary builder - Lanzer, Harriette (Oxford University Press, 1995)
The German Vocabulary Builder is an excellent guide for students, helping them to build up their German vocabulary, as well as preparing them for written and oral examinations. It includes over 3,000 words and phrases covering all curriculum topics, including home, animals, hobbies, food, travel, weather, work, media, current affairs, and environment. It features special sections on adjectives and verbs, activities, helpful tips and cartoon strips in each section to make learning fun. It contains material pitched at various levels so students of all abilities will benefit